PEMBERDAYAAN MASYARAKAT BERBASIS POTENSI LOKAL DESA DALAM UPAYA PELESTARIAN LINGKUNGAN HIDUP DAN KEHUTANAN DI DESA TANJUNG SARI KECAMATAN PABUARAN-KABUPATEN SERANG - Ita Rosita Wahyiah; Dita Rahayu; Chrisjhon Indra Imanuel; Safira Britantia De Fretes; Vety Reza (Indonesian Collaboration Journal of Community Services, 2023)
The forest is a fairly large area in which there are wood, plants and everything in it, as a whole, they are living things that provide many benefits to humans in the surrounding environment. Tanjung Sari Village has a beautiful atmosphere, to maintain beauty and concern for the environment, one effort that can be done is to provide counseling and assistance related to environmental and forestry preservation in the village so that its beauty is maintained. So the purpose of this community empowerment is to provide assistance to increase understanding regarding environmental preservation and forest potential for the people of Tanjung Sari Village. Counseling was carried out on July 21, 2023 using the implementation method through: material delivery seminars, discussions, practice with direct tree planting by community members, mentoring, monitoring and evaluation. The results of this assistance show that there is a lack of community awareness in developing existing potential related to forest conservation by planting trees directly, it can be seen that the community is reluctant to plant large woody trees such as extinct island, albasiah and other forest trees